Fine-Scale Heterogeneity of a Cold-Water Coral Reef and Its Influence on the Distribution of Associated Taxa - Price, David M.; Lim, Aaron; Callaway, Alexander; Eichhorn, Markus P.; Wheeler, Andrew J.; Lo Iacono, Claudio; Huvenne, Veerle A. I. (Frontiers in Marine Science, 2021)
Benthic fauna form spatial patterns which are the result of both biotic and abiotic processes. Within landscape ecology a range of descriptors have been used to infer the processes underlying spatial patterning, but only more recently have these been applied to marine habitats through the use of photomosaics, notably in shallow-water coral reef research. Fine- to medium-scale spatial patterns (<1-10 metres) have seldom been quantified in deep-sea habitats, but can provide fundamental ecological insights into species’ niches and interactions. Cold-water coral reefs formed by Desmophyllum pertusum (syn: Lophelia pertusa) and Madrepora oculata are traditionally mapped and surveyed with multibeam echosounders and video transects, which limit the ability to achieve the resolution and/or coverage to undertake fine-scale, centimetric quantification of spatial patterns. However, photomosaics constructed from imagery collected with remotely operated vehicles (ROVs) or autonomous underwater vehicles (AUVs), are becoming a prevalent research tool and can reveal novel information at the scale of individual coral colonies. A survey using a downwards facing camera mounted on a ROV traversed the Piddington Mound (Belgica Mound Province, NE Atlantic) in a lawnmower pattern in order to create 3D reconstructions of the reef with Structure-from-Motion techniques. Three high resolution orthorectified photomosaics and digital elevation models (DEM) >200 m2 were created and all organisms were geotagged in order to illustrate their point pattern. The Pair Correlation function was used to establish whether organisms were distributed with complete spatial randomness (CSR) or demonstrated a clustered pattern. We further applied a point pattern modelling approach to identify four potential point patterns: CSR, an inhomogeneous pattern influenced by environmental drivers, random clustered point pattern indicating biological clustering and an inhomogeneous clustered point pattern driven by a combination of environmental drivers and biological effects. Reef framework presence and structural complexity determined inhabitant distribution with most organisms showing a departure from CSR. This indicates affinity to local environmental drivers and/or restricted dispersion reproductive strategies within the habitat across a range of fine to medium scales. These data provide novel and detailed insights into fine-scale habitat heterogeneity and microhabitats showing that non-random distributions are apparent at these fine scales in deep-sea habitats.